[Sugarworker on a cattle drawn cart] - (:unkn) unknown (Pereira and Co. Ltd., 2009)
Man transporting harvested sugar cane on an animal drawn cart. Affixed to the postcard is a 15 cents Surinamese postage stamp
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sugarcane; Draft animals; Carriages and carts